Studi Awal Mikrozonasi dan Klasifikasi Site Wilayah Jakarta Selatan - Rifa Salma Salsabila; Bambang Sunardi; Setyoajie Prayoedhie (Jurnal Stasiun Geofisika Sleman, 2023)
Microzonation mapping is very necessary in the south Jakarta area because the effects of earthquakes are often felt. This region also has a very high population density. Microzonation is needed to reduce the risk if an earthquake occurs. Another effort to support earthquake microzonation is by conducting site classification. One of the data that can be used is microtremors which are then processed using the Horizontal to Vertical Spectral Ratio (HVSR) method. Furthermore, the HVSR inversion process can be used to obtain the value of the shear wave velocity (Vs). In this research, the creation of a microzonation map includes a dominant frequency map, amplification factor, seismic vulnerability index, and site classification map. The research results show that in the South Jakarta area, especially the Pesangrahan, Kebayoran Lama, Kebayoran Baru, Setiabudi and Tebet districts, the dominant frequency (fo) is relatively low, the amplification factor is relatively high, and the dominant site is classified as medium soil (SD). Based on this, in general the South Jakarta area has a relatively high risk of earthquakes.